Anti-Corruption as Value Learning in Senior High School - Montessori, Maria (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to analyze the learning of Pancasila and Civic Education about anti-corruption at senior high schools. The research method used was qualitative research whose informants include: teachers, school principals, and students. Data were collected by observation, interview and documentation study. Checking the validity of the data was carried out through triangulation and data analysis using the stages of data collection, data reduction, data presentation and conclusion drawing. The results showed that the implementation of anti-corruption learning in schools did not describe the implementation of learning about values which was not only a transfer of knowledge but also a transfer of values to students. Learning that is more focused on the cognitive dimension is found starting from the preparation of learning designs, implementing learning to the evaluation system used by the teacher.